2016
DOI: 10.1016/j.ijrobp.2016.06.762
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Radiation Dose and Microbleed Formation in Patients With Malignant Glioma

Abstract: Background: Cranial irradiation is associated with long-term cognitive changes. Cerebral microbleeds (CMBs) have been identified on susceptibility-weighted MRI (SWI) in patients who have received prior cranial radiation, and serve as radiographic markers for microvascular injury thought to contribute to late cognitive decline. The relationship between CMB formation and radiation dose has not previously been quantified. Methods: SWI was performed on 13 patients with stable WHO grade III-IV gliomas between 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Thus these sequences can be used to identify hemorrhage and necrosis with mineralization in affected subjects. The SWI sequence is routinely used in clinical practice to identify blood products and small-volume microhemorrhages in human patients, and SWI hypointensities have been reported in cancer patients receiving brain radiotherapy (73,74,77,78,(84)(85)(86)(87)(88). Use of these non-invasive, in vivo imaging protocols allows for monitoring of the progression of brain pathology longitudinally, often years prior to death, and offers the potential to map MRI abnormalities to neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus these sequences can be used to identify hemorrhage and necrosis with mineralization in affected subjects. The SWI sequence is routinely used in clinical practice to identify blood products and small-volume microhemorrhages in human patients, and SWI hypointensities have been reported in cancer patients receiving brain radiotherapy (73,74,77,78,(84)(85)(86)(87)(88). Use of these non-invasive, in vivo imaging protocols allows for monitoring of the progression of brain pathology longitudinally, often years prior to death, and offers the potential to map MRI abnormalities to neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Although the long-term consequences of single-highdose TBI on the adult brain are unclear, fWBI for the treatment of brain cancer may result in neuroinflammation, white matter necrosis, vascular injury and cognitive impairment (69)(70)(71)(72). In affected patients, scattered foci of hemorrhage and necrosis consistent with small blood vessel injury are detectable on susceptibility-weighted (SWI) magnetic resonance images (MRI) (73)(74)(75)(76)(77)(78). In the current study, we hypothesized that non-human primate long-term survivors of high-dose TBI would develop lesions on imaging that were similar to those observed after fWBI, although less severe and with a longer latency period.…”
Section: Introductionmentioning
confidence: 93%
“…These negative findings likely reflect the unsuitability of this measure for patients treated with focal RT since the dose is distributed nonuniformly and the spatial extent varies with tumor volume. The volume of the higher dose region should be a more appropriate metric for evaluation, as Wahl et al in 2017 found significantly more CMBs in this region in the first 3 years following RT. Unfortunately, radiation dosimetry maps were not available for enough patients included in our analysis to appropriately assess associations between CMB development and dosimetry volumes and/or the extent of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These can be detected with susceptibility‐weighted imaging (SWI) as early as 8 months following treatment, although in most adult patients the onset of vascular injury is usually observed 2 years post‐RT . Prior smaller studies have shown increases in the formation of CMBs over time in patients treated with RT for malignant gliomas that were spatially dependent on the RT dose, and an absence of CMBs in patients treated with chemotherapy alone . One of the largest and most comprehensive studies to date in adult survivors of childhood brain tumors reported increases in total CMB burden with accumulated time since RT and with greater spatial extent of treatment .…”
mentioning
confidence: 99%
“…Intracerebral microbleeds generally occur several years postradiation, with a cumulative incidence ranging from 40% to 90% by 5-10 years after radiation, with the detection range dependent on the sensitivity of the imaging technique; for example, susceptibility-weighted imaging is superior to T2*-weighted gradient echo. [63][64][65]…”
Section: Microbleedsmentioning
confidence: 99%